Clinical Reasoning: Patient With Prior Spinal Cord Injury Who Developed Altered Mental Status After a Fall. (13th December 2022) - Dessy, Alexa; Bhagat, Dhristie; Czeisler, Barry M.
Abstract : An 18-year-old man with a history of complete traumatic spinal cord injury (SCI) at C5-C7 3 years before presented with unresponsiveness and hypoxia after a fall. There were no overt signs of bruising or swelling. After extensive and unrevealing initial workup, MRI brain without contrast showed numerous diffusely scattered punctate foci of diffusion restriction and evidence of numerous microhemorrhages. A full body skeletal survey revealed mildly affected, nondisplaced, incomplete fractures in the distal femoral metaphyses bilaterally. This case presentation discusses specific considerations for patients with SCI, reviewing the differential diagnosis, workup, and management of altered mental status after minor falls or other trauma in this population.